Exploring students' general chemistry concept in high school - Javien, Arnel A. (Animo Repository, 2005)
A study that aimed to probe students’ concept understanding on chemistry and to explore the common alternative conception and misconceptions of high school chemistry was conducted from January to May 2005. Descriptive survey was used in this research to explore the alternative conceptions and misconceptions of students in chemistry. The study used junior class, Don Ramon E. Costales Memorial National High School with 21 males and 31 females. A public school located at the municipality of Villasis under the Division Pangasinan II Region 1. Data collected were analyzed quantitatively and qualitatively based upon the students’ responses from the 20 item two-tier High School Chemistry Concepts Inventory (HSCCI) and from the structured interview that were conducted to selected students 10 students The finding showed that alternative misconceptions on different topics in chemistry are common to third year students in chemistry. The top five prevalent incorrect responses in HSCCI. . Based in the incorrect responses of the students and their reasons in the test, the topic Classifying matter the highest percentage 82.69% of the students got it incorrect. Then the second topic was Order Among Elements got 67.31%. The third in rank was the topic Solution got 61.54%respondent. The fourth rank was also in solution got 59.62% of the respondents. The fifth was the topic Changes in matter got 57.31%. The result in the level understanding revealed that majority of the students has a partial understanding with specific misconceptions (PU/SM) and specific misconceptions (SM) in the different topics given in the two- tier HSCCI.